Africa and the Bible - Yamauchi, Edwin M. (Grand Rapids, MI Baker Academic, 2004)
Includes bibliographical references and indexes.
Keywords: Bible -- Black interpretations; Afrocentrism -- religious aspects -- Christianity; Bible -- criticism, interpretation, etc